2022
DOI: 10.1038/s41746-022-00735-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with long-term use of digital devices in the electronic Framingham Heart Study

Abstract: Long-term use of digital devices is critical for successful clinical or research use, but digital health studies are challenged by a rapid drop-off in participation. A nested e-cohort (eFHS) is embedded in the Framingham Heart Study and uses three system components: a new smartphone app, a digital blood pressure (BP) cuff, and a smartwatch. This study aims to identify factors associated with the use of individual eFHS system components over 1-year. Among 1948 eFHS enrollees, we examine participants who returne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…Third, most individuals included were White, and there was minimal representation of Hispanic individuals. Although the absolute number of individuals in our study from racial minority groups compares favorably to prior studies of wearable technology, 6 , 7 our findings may not generalize to populations with varying racial and ethnic composition. Fourth, we studied a sample of longitudinal primary care and cardiology patients having a specific comorbidity profile that may differ from other populations.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Third, most individuals included were White, and there was minimal representation of Hispanic individuals. Although the absolute number of individuals in our study from racial minority groups compares favorably to prior studies of wearable technology, 6 , 7 our findings may not generalize to populations with varying racial and ethnic composition. Fourth, we studied a sample of longitudinal primary care and cardiology patients having a specific comorbidity profile that may differ from other populations.…”
Section: Discussioncontrasting
confidence: 72%
“…A recent analysis of ≈2000 individuals from the Framingham research cohort found that age, sex, and educational attainment were each associated with digital health engagement. 6 A second survey‐based study including just >1200 respondents reported that patients with atrial fibrillation were more likely to share wearable device data with their health care providers. 7 A nationally representative survey relying solely on self‐reported data found that an estimated 29% of individuals use wearable devices, and that those with cardiovascular conditions had a lower prevalence of device use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 52 Higher depressive symptoms have been associated with lower engagement with digital device use. 53 , 54 Targeted interventional strategies to support digital device use may result in improvement in regular and longer-term self-home BP management in this group. Interventions could also address disparities in age, educational attainment, and household income, which are known to be associated with lower wearable device use.…”
Section: Discussionmentioning
confidence: 99%